Pemisahan Oli Bekas Menggunakan Alat Separator dengan Media Pemisah Karbon Aktif dan Kardus Bekas - Nur Hasanah, Mutia; Fauzan, Reza; Putra, Alfian (Jurnal Teknologi, 2024)
This research was conducted to separate used oil using a separator with activated carbon separation media and used cardboard. The treatment was carried out with time variations (minutes) 5, 10, 15, 20, and 25. With variations in the composition of used oil 2%, 4%, 6%, 8%, and 10%. Oil collection as a sample was carried out at a motorcycle workshop in Gampong Java, Banda Sakti District, Lhokseumawe City. The results of the study were tested for characteristics, pH, total dissolved solid (TDS), turbidity, and chemical oxygen demand (COD) in accordance with quality standards. These results show that pH, turbidity and TDS decrease with the longer the time left for sampling the separation results. Meanwhile, TDS and COD there are some samples that are still slightly below standard. With the influence of the residence time of sampling of sampling separation results, the results of the characteristic test are getting better and more stable. The results of this study show that used oil separation media using activated carbon and used cardboard can be used as a prevention of environmental pollution.